Cell‐Based Optimization of Covalent Reversible Ketoamide Inhibitors Bridging the Unprimed to the Primed Site of the Proteasome β5 Subunit. (12th November 2019) - Stubba, Daniel; Bensinger, Dennis; Steinbacher, Janika; Proskurjakov, Lilia; Salcedo Gómez, Álvaro; Schmidt, Uwe; Roth, Stefan; Schmitz, Katja; Schmidt, Boris
Abstract: The ubiquitin‐proteasome system (UPS) is an established therapeutic target for approved drugs to treat selected hematologic malignancies. While drug discovery targeting the UPS focuses on irreversibly binding epoxyketones and slowly‐reversibly binding boronates, optimization of novel covalent‐reversibly binding warheads remains largely unattended. We previously reported α‐ketoamides to be a promising reversible lead motif, yet the cytotoxic activity required further optimization. This work focuses on the lead optimization of phenoxy‐substituted α‐ketoamides combining the structure‐activity relationships from the primed and the non‐primed site of the proteasome β5 subunit. Our optimization strategy is accompanied by molecular modeling, suggesting occupation of P1′ by a 3‐phenoxy group to increase β5 inhibition and cytotoxic activity in leukemia cell lines. Key compounds were further profiled for time‐dependent inhibition of cellular substrate conversion. Furthermore, the α‐ketoamide lead structure 27 does not affect escape response behavior in Danio rerio embryos, in contrast to bortezomib, which suggests increased target specificity. Abstract : Bridging the gap : We report the identification of novel covalent reversible binding P1′‐site extended α‐ketoamide inhibitors for the proteasome β5 subunit. The development was guided by a new in‐cell proteasome inhibition assay and the lead compound was profiled in a Danio rerio embryo escape response assay showing superior properties in comparison to bortezomib. BODIPY conjugated activity‐based probes give insight into in‐cell localization and distribution in zebrafish embryos.